THE SOCIAL AND ENVIROMENT RESPONSIBILITY OF PLANTATION COMPANY AND OIL PALM MANUFACTURER IN SIAK DISTRICT - Resky Pratama Saputra; Fahmi Fahmi; Yeni Triana (STIH Putri Maharaja, 2021)
Based on Article 74 Paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies, it is stipulated that companies that carry out their business activities in the field of natural resources and / or fields related to natural resources are obliged to carry out social and environmental responsibility. This research aims to explain the social and environmental responsibility of plantation companies and oil palm mills in Siak Regency based on Law Number 40 of 2007 concerning Limited Liability Companies. The method used in this research is socio-legal research. The results of the research explained that the social and environmental responsibility of the plantation company and palm oil mill PT Teguh Karsa Wana Lestari in Siak Regency based on Law Number 40 of 2007 concerning Limited Liability Companies isn’t yet implemented. Legal sanctions for oil palm plantation and mill company PT Teguh Karsa Wana Lestari in Siak Regency are companies that don’t carry out social responsibility are subject to administrative sanctions based on Law Number 40 of 2007 concerning Limited Liability Companies, while companies that don’t carry out their responsibilities environment can be subject to criminal sanctions based on Law Number 32 of 2009 concerning Environmental Protection and Management.